Comparison of different assays for the detection of anticyclic citrullinated peptide antibodies in patients with rheumatoid arthritis - Ma, Lisha; Wang, Wensheng; Li, Lisha; Chen, Ying; Chen, Binxuan; Shao, Miaoli; Cheng, Yongjun; Zhou, Renfang (Frontiers in Immunology, 2022)
Objective: To evaluate a novel fully automated immunoturbidimetric assay developed by Qiangsheng Biotechnology Company for the detection of anticyclic citrullinated peptide antibodies (anti-CCP) in serum of patients with rheumatoid arthritis (RA) and compare it to the conventional EUROIMMUN- anti-CCP ELISA. Two other commonly used automated assays, the Elecsys anti-CCP assay, an ECLIA that is run on the Modular Analystics E170 (Cobas Diagnostics, Germany), and an anti-CCP CLIA developed by YHLO that is run on the iFlash 3000 Chemiluminescence Immunoassay Analyzer, were included as reference standards. Methods: A total of 264 serum samples were collected from patients attending the First People’s Hospital of Wenling affiliated to Wenzhou Medical University between July 2020 and November 2020. These included 131 serum samples collected from patients with RA, 70 serum samples collected from patients with other autoimmune diseases, and 63 serum samples collected from healthy controls at a physical examination. The clinical performance and sensitivity and specificity of the four anti-CCP assays for the diagnosis of RA were compared using receiver operating characteristic (ROC) curve analysis. Results: The Kappa statistic indicated almost perfect agreement between the EUROIMMUN-anti-CCP ELISA and the Elecsys anti-CCP ECLIA (Cobas) (0.863), the EUROIMMUN-anti-CCP ELISA and the anti-CCP CLIA (YHLO) (0.862), and the Elecsys anti-CCP ECLIA (Cobas) and the anti-CCP CLIA (YHLO) (0.816). On ROC curve analysis, AUC values were 0.955 for the EUROIMMUN-anti-CCP ELISA, 0.948 for the anti-CCP CLIA (YHLO), 0.947 for the Elecsys anti-CCP ECLIA (Cobas) and 0.903 for Qiangsheng, indicating all the assays had a good diagnostic performance for RA. Conclusion: The anti-CCP assays provided similar diagnostic information. The novel fully automated immunoturbidimetric assay for anti-CCP developed by Qiangsheng Biotechnology Company may be especially useful for large scale clinical screening in RA as it has a shorter testing time than the commercially available alternatives.